In my attempt to prove that $\Gamma'(1)=-\gamma$, I've reduced the problem to proving that $\lim_{n\rightarrow\infty}(\frac{\Gamma '(n+1)}{n!} -\log(n))=0$.

Where $\gamma$ is the Euler-Mascheroni constant, and $\log$ denotes the natural logarithm.

I've been messing with it for a while without achieving much of anything. The first derivative of the Gamma function does have a recursive formula which can be found through iterated integration by parts, but that was what I used to get where I am, and applying it again just takes me back to where I started.

My book lists a ton of equivalent definitions for the Gamma function, but only gives the integral definition for its derivatives and I've just had considerable trouble doing much with that integral.

I should note that at first I was trying to prove that $\frac{\Gamma'(n+1)}{n!}\sim\log(n)$, but now I'm pretty sure that showing that their difference in the limit is zero would be sufficient, since what I'm ultimately interested in is showing that $\lim_{n\rightarrow\infty}(-\sum_{k=0}^n\frac{1}{k} +\frac{1}{n!}\Gamma'(n+1)) =-\gamma$

Hopefully someone can help me with this. Thanks.


We have $\log(\Gamma(n+2))-\log(\Gamma(n+1))=\log(n+1)$, so by the mean value theorem, $\frac{\Gamma'}{\Gamma}(s)=\log(n+1)$ for some $s\in[n+1,n+2]$. Now, $\frac{\Gamma'}{\Gamma}$ is increasing, so repeating the argument on the interval $[n,n+1]$, we get $\log(n)\leq\frac{\Gamma'}{\Gamma}(n+1)\leq \log(n+1)$. The result now follows, as $\lim_{n\to\infty}\log(n+1)-\log(n)=0$.

| cite | improve this answer | |
  • $\begingroup$ @C.Williamson $\Gamma(n+2) = (n+1) \Gamma(n+1)$, hence $\log\Gamma(n+2) = \log\Gamma(n+1) + \log(n+1)$. $\endgroup$ – Sasha Aug 16 '12 at 23:30
  • $\begingroup$ Yeah, I deleted my comment after seeing my mistake. I like the answer! $\endgroup$ – N. Mao Aug 16 '12 at 23:32
  • $\begingroup$ Wow, this is a really clever use of the MVT, thanks. $\endgroup$ – Thoth Aug 16 '12 at 23:35

If what you want is to prove that $\Gamma'(1)=-\gamma$, I will show you a very slick solution I learned from user robjohn.

(I guess) you know that $$\int_0^1 \frac{1-x^n}{1-x}dx=H_n$$

(just expand the function it is easy) Now look at

$$I(n)=\int_0^1 x^{n}\log(1-x)dx$$

We integrate by parts, to get

$$I(n)=\int_0^1 x^{n}\log(1-x)dx=\left.\frac{1-x^{n+1}}{n+1}\log(1-x)\right|_0^1- \frac 1{n+1}\int_0^1 \frac{1-x^{n+1}}{1-x}dx$$

$$I(n)=\int_0^1 x^{n}\log(1-x)dx=-\frac 1{n+1}\int_0^1 \frac{1-x^{n+1}}{1-x}dx$$

$$I(n)=\int_0^1 x^{n}\log(1-x)dx=-\frac {H_{n+1}}{n+1}$$

Now let $x=1-u$, then $un=m$,

$$I(n)=\int_0^1 (1-u)^{n}\log(u)du$$

$$I(n)=\frac 1 n\int_0^n \left(1-\frac m n\right)^{n}\log\left(\frac m n\right)dm$$

$$I(n)=\frac 1 n\int_0^n \left(1-\frac m n\right)^{n}\log ( m )dm-\frac 1 n\int_0^n \left(1-\frac m n\right)^{n}\log( n)dm$$

Now we use the last equiality we derived, to start getting into something:

$$-\frac {n}{n+1}H_{n+1}=\int_0^n \left(1-\frac m n\right)^{n}\log ( m )dm-\log n \int_0^n \left(1-\frac m n\right)^{n}dm$$

Now the rightmost integral is just

$$\int_0^n {{{\left( {1 - \frac{m}{n}} \right)}^n}} dm = n\int_0^1 {{{\left( {1 - u} \right)}^n}} du = n\int_0^1 {{u^n}} du = \frac{n}{{n + 1}}$$

$$-\frac{n}{{n + 1}}{H_{n + 1}} = \int_0^n {{{\left( {1 - \frac{m}{n}} \right)}^n}} \log mdm - \frac{n}{{n + 1}}\log n$$

So we get

$$\frac{n}{{n + 1}}\left( {\log n - {H_{n + 1}}} \right) = \int_0^n {{{\left( {1 - \frac{m}{n}} \right)}^n}} \log mdm$$

Now, by letting $n\to \infty$, we get

$$\eqalign{ & \mathop {\lim }\limits_{n \to \infty } \frac{n}{{n + 1}}\left( {\log n - {H_{n + 1}}} \right) = \mathop {\lim }\limits_{n \to \infty } \int_0^n {{{\left( {1 - \frac{m}{n}} \right)}^n}} \log mdm \cr & - \gamma = \mathop {\lim }\limits_{n \to \infty } \int_0^n {{{\left( {1 - \frac{m}{n}} \right)}^n}} \log mdm \cr & - \gamma = \int_0^\infty {{e^{ - m}}} \log mdm \cr} $$


$$\Gamma '\left( n \right) = \int_0^\infty {{e^{ - m}}} {m^{n - 1}}\log mdm \Rightarrow \Gamma '\left( 1 \right) = \int_0^\infty {{e^{ - m}}} \log mdm$$

| cite | improve this answer | |


where $\psi(x)$ is the digamma function, i.e. the logarithmic derivative of $\Gamma(x)$. Then

$$ \lim_{x \to \infty}\frac{\Gamma'(x+1)}{x!}-\log(x)= \lim_{x \to \infty}\frac{\Gamma(x+1)\psi(x+1)}{\Gamma(x+1)}-\log(x)= \lim_{x \to \infty}\psi(x+1)-\log(x) $$

Noting $$\psi(x+1) = \log x+O\left(\frac{1}{x}\right)$$

We conclude

$$\lim_{x \to \infty}\psi(x+1)-\log(x)=0$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.